2017
DOI: 10.1063/1.4983013
|View full text |Cite
|
Sign up to set email alerts
|

Precise thickness control in recess etching of AlGaN/GaN hetero-structure using photocarrier-regulated electrochemical process

Abstract: The photocarrier-regulated electrochemical (PREC) process was developed for fabricating recessed-gate AlGaN/GaN high-electron-mobility transistors (HEMTs) for normally off operation. The PREC process is based on photo-assisted electrochemical etching using low-energy chemical reactions. The fundamental photo-electrochemical measurements on AlGaN/GaN heterostructures revealed that the photo-carriers generated in the top AlGaN layer caused homogeneous etching of AlGaN with a smooth surface, but those generated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…We also confirmed that the bumps can be removed by the HCl-H2O2 post cleaning process accompanied with removing the Ti mask. Furthermore, in contactless PEC etching, the etched depth showed a self-stopping feature similar to that observed in conventional PEC etching [12,17]. The dependence of the offset between the SiO2 mask and the Ti cathode pad in terms of the fineness of the etched patterns, and the lifetime of the electrolyte remains unclear.…”
Section: Cathode Design For Contactless Pec Etching For Rf Devicesmentioning
confidence: 72%
See 3 more Smart Citations
“…We also confirmed that the bumps can be removed by the HCl-H2O2 post cleaning process accompanied with removing the Ti mask. Furthermore, in contactless PEC etching, the etched depth showed a self-stopping feature similar to that observed in conventional PEC etching [12,17]. The dependence of the offset between the SiO2 mask and the Ti cathode pad in terms of the fineness of the etched patterns, and the lifetime of the electrolyte remains unclear.…”
Section: Cathode Design For Contactless Pec Etching For Rf Devicesmentioning
confidence: 72%
“…This oxide dissolves in acids or bases. An anodic oxidation process therefore serves as the basis of PEC etching of GaN [12,14,18,19]. The overall etching reaction for GaN, in which…”
Section: A Fundamentals Of Conventional Pec Etchingmentioning
confidence: 99%
See 2 more Smart Citations
“…After early studies by Minsky [5] and Youtsey [6], various PEC etching processes have been reported for GaN [7][8][9] and AlGaN [10] with growing interest in damage-less etching. Our PEC etching [11][12][13][14], which is carried out using the pulsed bias, is a cyclic process consisting of anodic oxidation and subsequent dissolution of the resulting oxide in an electrolyte. We reported that the dry-etching damage was effectively removed from n-GaN surfaces with the PEC process without causing any additional damage [11].…”
Section: Introductionmentioning
confidence: 99%